Hippocampal and Congenital Brain Malformations - J Gordon Millichap (Pediatric Neurology Briefs)
Sixty two patients, aged 15 days to 18 years, with congenital brain malformations were evaluated retrospectively to determine the association of various brain malformations with hippocampal abnormalities, in a study at Baskent University, Ankara, Turkey.